THE INFLUENCE OF DISCOVERY LEARNING MODEL ON STUDENTS 4C THINKING SKILLS: META-ANALYSIS - Herson Anwar; Arifin; Budi Mardikawati; Titik Purwati; Nenni Triana; Rusmawan; Tomi Apra Santosa (International Journal of Teaching and Learning, 2023)
In 21st century learning, students must have Critical Thinking, Creative Thinking, Collaborative and Communicative, better known as 4C skills. 4C skills help students provide solutions in solving a problem. However, teachers have not been able to stimulate students to have 4C thinking skills. The discovery model is one model that is effective in encouraging students to think 4C. The aim of this research is to determine the effect of the discovery learning model on students' 4c thinking abilities. This type of research is meta-analysis research. Data sources come from 10 national and international journals. Search for data sources via Google Scholar, ERIC, ScienceDirect, DOAJ, and Wiley databases. The data collection technique is direct observation through databases and documentation. The data analysis technique calculates the effect size value with the help of the JASP application. The research results concluded that the average score for critical thinking was 82.17, creative thinking 80.52, communication 85.16, and collaboration 80.57. Furthermore, the average effect size value is 1.017 with high criteria. These findings explain that the discovery learning model has a significant effect on students' 4c thinking abilities.